2016
DOI: 10.1016/j.dsp.2016.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a digital transmitter leakage LMS-based cancellation algorithm for multi-standard radio-frequency transceivers

Abstract: International audienceThis paper deals with a joint estimation algorithm that is dedicated to digital compensation of transmitter leakage pollution in frequency division duplexing transceivers. These transceivers are affected by transmitter to receiver signal leakage. Combined with the nonlinearity of amplifying components in the receiver path, the baseband signal received can be severely polluted by a baseband polluting term. This term is based on the square modulus of the transmitted signal, and it depends o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…We have proposed in [13] a TxL interference compensation based on two reference-based LMS algorithms that jointly estimates the complex gain and fractional delay of the TxL channel. The proposed algorithm can estimate timevarying parameters estimation, as presented in [12] with the tracking of the complex gain. We have shown that an optimal step-size for the complex gain estimation stage can be obtained.…”
Section: Baseband Model and Issuesmentioning
confidence: 99%
See 3 more Smart Citations
“…We have proposed in [13] a TxL interference compensation based on two reference-based LMS algorithms that jointly estimates the complex gain and fractional delay of the TxL channel. The proposed algorithm can estimate timevarying parameters estimation, as presented in [12] with the tracking of the complex gain. We have shown that an optimal step-size for the complex gain estimation stage can be obtained.…”
Section: Baseband Model and Issuesmentioning
confidence: 99%
“…In this paper, we complete the performance analysis of our previously proposed joint estimation (JE) algorithm dedicated to Tx leakage compensation [12,13]. This algorithm estimates the equivalent TxL channel (approximated by a time varying complex gain and a fractional delay (FD)).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The baseband polluting term depends on the equivalent Tx leakage channel, modeling leakages and the received path. We have proposed in [7,8] a joint estimation of the complex gain and the fractional delay and derived asymptotic performance of the complex gain estimator, that showed the necessity of the fractional delay estimation. In this paper, we propose a comprehensive study of the fractional delay estimation algorithm and its analytic performance.…”
mentioning
confidence: 99%